(untitled) (Texas Journal of Engineering and Technology, 2023)
In the article, it is proved that the C=H bond intensive absorption characteristic for the imidozoline family is more in the sample obtained by acid catalysis. In this, C= H - and C=O- we see that the absorption intensities for the bonds are interrelated, as the intensity of one bond increases, that of the other decreases. It is possible to prove the existence of imidazaline derivatives as a result of comparison of C=H bond intensities in the IR spectra of the studied samples under different conditions.